668 The Consequences to Emergency Surgery During COVID19 Pandemic in a UK District General Hospital in The North East of England. (4th May 2021) - Evans, R; Ng, C
Abstract: Aim: COVID19 pandemic has significantly affected surgical services. We aim to review its effects on our theatre output and risk of encountering COVID 19 cases. Method: Serial record of operations performed locally were reviewed from start of UK COVID19 pandemic lockdown on 23rd March 2020 to 13th July 2020 after it was lifted. A weekly average by month of operations and the percentage of COVID19 cases diagnosed within 30 days of the procedure were noted. Results: 733 operations performed through this period. In March, 33 operations/week performed, 88.4% emergency and 7% diagnosed with COVID19. April, 31 operations /week performed, 95.9% emergency and 10.6% diagnosed with COVID19. May 46 operations /week performed, 94.5% emergency and 3.3% diagnosed with COVID19. June 56 operations /week, 80.9% emergency and less than 0.01% diagnosed with COVID19. By July 80 operations/week, 59.4% emergency and none diagnosed with COVID 19. Since testing capacity increased, only 6 of the 27 operated were diagnosed with COVID19. Conclusions: There was initial reduction to non-emergency workload. However, this has gradually shifted as protocols are in place improve public confidence to return for surgical treatment. Mandatory admission testing allows early identification and remains essential for planning of services and protecting the workforce.